Scientific and Pedagogical Basis of the Activities of Physical Education Teachers (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In this article, the main terms encountered in the scientific pedagogical activity of the future physical training teacher, the correct organization of pedagogical activity, the future of physical training teachers in the course of scientific pedagogical activity aspects to be considered and what approach is needed, as well as the organization of innovative and technological activities of the future physical education teacher.